Synthesis and olfactory evaluation of homologous series of (+)‐ and (−)‐carvone oxime ethers. (25th September 2015) - Strub, Daniel Jan; Kula, Józef; Sikora, Magdalena; Gibka, Julia; Lochyński, Stanisław
Abstract: Novel semi‐synthetic fragrant compounds were prepared from both isomers of carvone. Deprotonation of (+) and (−)‐carvone oximes with sodium hydride and subsequent O ‐Alkylation with various alkyl halides in DMSO resulted in 18 ethers. Scents of most synthesized compounds are agreeable. A shift of fragrance is observed between substrates. The scent of (−)‐carvone resembles that of spearmint and (+)‐carvone – caraway. The fragrance of carvone oximes is similar, vegetable‐like. Significant differences were observed between homologous series of carvone oxime ethers. Their odours range from vegetable‐like (pickled cucumber, leaves of horseradish and carrot, scallion and onion) and herbaceous to sulphuric, floral (lily) and fruity (blackcurrant and pear). Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Novel oxime ethers were prepared from both isomers of carvone. Their odours range from vegetable‐like and herbaceous to sulphuric, floral and fruity.